Implementation Of The Policy Of The Minister Of Law and Human Rights Regulation Number 11 Of 2017 - Emirza Henderlan Harahap (International Journal of Law and Society, 2025)
Overcrowded condition is a condition where correctional institutions or State Detention Centers have too large a capacity because the increasing number of inmates is not comparable to the prison or detention center facilities. Permenkumham Number 11 of 2017 is used as a reference for implementing an action plan for handling overcrowded in Indonesia, which includes four main programs: regulatory arrangement, institutional strengthening, provision of infrastructure, and empowerment of human resources. This study aims to identify the methods used to handle overcrowded residents in Class II B Pemalang Detention Center and to find barriers that hinder the process. The researcher used a qualitative research method to determine the factors that hinder the implementation of handling overcrowded residents in Class II B Pemalang Detention Center. The results of the study indicate that handling overcrowded residents in Class II B Pemalang Detention Center has been going well because of remissions, solid internal institutions, good relationships with government institutions or organizations, and empowerment of correctional officers. In addition, handling overcrowded residents in Class II B Pemalang Detention Center faces several obstacles. One of them is the number of correctional officers which is too many compared to the number of prison inmates, as well as facilities and infrastructure which are not optimal.